Prevalence of different tick species on livestock and associated equines and canine from different agro-ecological zones of Pakistan - Hussain, Nazeer; Shabbir, Rana Muhammad Kamran; Ahmed, Haroon; Afzal, Muhammad Sohail; Ullah, Shafi; Ali, Abid; Irum, Shumaila; Naqvi, Syed Kamran-ul-Hassan; Yin, Jianhai; Cao, Jianping (Frontiers in Veterinary Science, 2023)
Ticks are ectoparasites that act as vectors for transmission of various diseases in wild and domesticated animals and pose a serious threat to human health. Because of the hot and humid conditions in different agro-ecological zones of Pakistan, ticks are abundant and parasitize a variety of animals. The aim of this study was to identify tick species and their distribution on different livestock hosts, such as sheep, goat, cattle, buffalo, and camel, and livestock associated canines and equines, such as horse, donkey, and dog, across different agro-ecological zones of Pakistan. The ticks were collected, and tick prevalence data were recorded and analyzed. The ticks were morphologically analyzed using stereomicroscope and morphological keys. A total of 2846 animals were examined, and 408 animals were tick-infested. Eleven tick species belonging to 4 genera were identified: Hyalomma anatolicum, Hyalomma scupense, Hyalomma dromedarii, Hyalomma isaaci, Rhipicephalus microplus, Rhipicephalus haemaphysaloides, Rhipicephalus turanicus, Haemaphysalis punctata, Haemaphysalis montgomeryi, Haemaphysalis bispinosa, and Ixodes sp. The overall tick prevalence was 14.33%; host-wise infestation rate was 12.17% in sheep; 12.59%, goat; 11.7%, buffalo; 11.67%, cattle; 19.6%, camel; 27.38%, donkey; 23.52%, horse; and 24.32%, dog. Tick infestation of different animals differed on the basis of the zones. Camels showed the highest tick infestation rate in zones 1 and 2 (21.42% and 26.66%, respectively), whereas donkeys showed the highest infestation rate in zones 3, 4, 6, and 7 (25%, 39.28%, 3.33%, and 21.42%, respectively). The infestation rates of Hyalomma and Rhipicephalus were the highest in zone 2 (71.43% and 52.94%, respectively). The infestation rate of Hyalomma was the highest (47.36%) in sheep; Haemaphysalis (46.87%), goat; Rhipicephalus (69.70%), buffalo; Rhipicephalus (62.27%), cattle; Hyalomma (70%), camel; Ixodes (60.86%), donkey; Ixodes (75%), horse; and Rhipicephalus (61.11%), dog. This study showed the diversity and infestation rate of different ticks with respect to their hosts and agro-ecological zones of Pakistan. High tick burdens and infestation rates are responsible for the spread of different tick-borne infections, resulting in loss of animal productivity and posing a threat to animal and human health. Understanding different tick species and their distribution across different zones will help to develop efficient control measures.